A Presumption of Choice: The Problem With Prevention. Issue 170 (5th January 2021) - Elkins, Becki; Hawkins, Beck
Abstract: This chapter highlights campus efforts to respond to alcohol use among students, distinguishes heavy drinkers from students with substance use disorders, and details why prevention efforts are insufficient for students in recovery.